Chemotherapy Combined With Surgery in a Case With Metanephric Adenoma - Hu, Shaohua; Zhao, Zhenli; Wan, Zhisheng; Bu, Weizhen; Chen, Songqiang; Lu, Yiqun (Frontiers in Pediatrics, 2022)
Background: Metanephric adenoma is an extremely rare renal neoplasm, especially in pediatrics. Chemotherapy combined with surgery in metanephric adenoma has not been reported. Methods: We describe a case of metanephric adenoma in a child less than 2 years old, which were treated by chemotherapy combined with surgery. Results: Nephron sparing surgery was performed after regular chemotherapy, and the pathological result was metanephric adenoma. Conclusions: Pediatric metanephric adenoma is extremely rare, the clinical manifestations and imaging examinations lack specificity. Nephron sparing surgery is recommended as the preferred treatment for metanephric adenoma. Long-term follow-up and more in-depth molecular genetic research are still needed to determine the benign or malignant of metanephric adenoma and whether chemotherapy drugs have an effect on it.